2018
DOI: 10.1016/j.jebo.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Broadband internet, digital temptations, and sleep

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 41 publications
4
29
0
3
Order By: Relevance
“…Sleep disturbance can be harmful, and influences hormonal function resulting in psychological and physiological impairment [34]. In line with previous evidence [11,12,32,35,36], the present study first showed that without adjusting for other variables, PIU was positively associated with sleep disturbance. Older adolescents were at a higher risk of sleep disturbance.…”
Section: Discussion and Implicationsupporting
confidence: 90%
See 1 more Smart Citation
“…Sleep disturbance can be harmful, and influences hormonal function resulting in psychological and physiological impairment [34]. In line with previous evidence [11,12,32,35,36], the present study first showed that without adjusting for other variables, PIU was positively associated with sleep disturbance. Older adolescents were at a higher risk of sleep disturbance.…”
Section: Discussion and Implicationsupporting
confidence: 90%
“…However, evidence suggests that sleep problems tend to increase during adolescence, and poor sleep quality and sleep disturbance among adolescents has been a major public health concern [9]. Sleep deprivation is related to low self-control that has been found to be associated with a range of behaviors including PIU among adolescents [10,11,12]. Prior studies reported that adolescents who spent more time using the Internet had less sleeping time, which may cause irregular sleep patterns [13].…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 presents an alternative specification where the number of landline broadband connections is instead instrumented. This use of internet penetration is not new in the literature, as it has been instrumented in a number of studies to predict participation in internet-mediated activities (see, for example, Billari et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Čini se da ograničena upotreba interneta može imati pozitivan efekat na mentalno blagostanje dece i mladih, a da dva ekstrema -apsolutno ne korišćenje ili preterano korišćenje mogu imati negativne efekte na mentalno blagostanje [8]. Izražena upotreba socijalnih medija je udružena sa slabijim spavanjem, a posebno je uočena veza između igranja video igrica u večernjim časovima i deprivacija spavanja [9].…”
Section: Pejović Milovančević M Mogu Li Mediji Biti Prijatelji Deci unclassified